Alliance Participation, Treaty Depth, and Military Spending. - Alley, Joshua (International Studies Quarterly, 2021)
How does alliance participation affect military spending? Some argue that alliance membership increases military expenditures, while others contend that it produces spending cuts. I argue that deep formal defense cooperation modifies the impact of alliance participation on military expenditures and can explain increases and decreases in spending by small alliance members. Security-seeking junior members of deep alliances usually decrease military spending because these treaties are more credible. Joining shallow alliances often increases junior alliance member military spending, however. I test the argument by creating a latent measure of alliance treaty depth and using it to predict differences in how alliance participation affects military spending. The research design generates new empirical evidence linking alliance participation and percentage changes in state military spending from 1919 to 2007. I find that deeper alliance treaties tend to decrease military spending by junior alliance members, and shallow alliances often increase military spending. These results help scholars and policymakers better understand a central question about alliance politics that has been debated in scholarship for decades.